Case Report: Immune-related eruptive keratoacanthoma with fungal coinfection under PD-1 inhibitor therapy: a diagnostic and therapeutic challenge - Su, Ying-Jie; Wu, Zheng; Hou, Yan-Li; Yan, Meng-Xia; Ma, Xiu-Mei; Lin, Hou-Wen (Frontiers in Pharmacology, 2025)
BackgroundIt has been reported that immunotherapy with programmed cell death protein 1 (PD-1) inhibitors (pembrolizumab or nivolumab) can induce multiple eruptive keratoacanthomas (KAs), representing an immune-related cutaneous adverse event (ircAE).MethodsThis case report describes a 63-year-old female with recurrent cervical adenocarcinoma who developed multiple eruptive KAs and a concurrent fungal infection following treatment with the PD-1 inhibitor zimberelimab. We analyzed the etiology, diagnosis, and treatment by integrating clinical manifestations, pathological examinations, previous treatment history, and a review of the literature.ResultsDespite an initial misdiagnosis as a fungal infection, multidisciplinary review identified KA as an ircAE. Topical corticosteroids led to resolution, and another PD-1 inhibitor was reintroduced without recurrence of cutaneous toxicity.ConclusionThis is the first documented case of eruptive KA linked to zimberelimab, expanding the spectrum of PD-1 inhibitor-associated ircAEs. A concurrent fungal infection obscured the diagnosis, delaying appropriate treatment and highlighting the importance of recognizing rare ircAEs and multidisciplinary collaboration.